Strategic Drivers of Academic Employee Performance in Higher Education - Masman, Ronnie Resdianto; Maupa, Haris (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study aims to examine how knowledge management and organizational commitment shape employee performance in higher education, while positioning organizational innovation as a contested mechanism within Resource-Based and Knowledge-Based frameworks. It advances a novel contribution by demonstrating that the strategic value of intangible assets does not necessarily operate through innovation, thereby challenging dominant linear assumptions in organizational theory. Using data from 200 respondents in higher education institutions in West Jakarta, the findings reveal that knowledge management and organizational commitment exert strong direct effects on both innovation and employee performance, while innovation fails to mediate these relationships. This asymmetry indicates that performance is more structurally driven by knowledge integration and organizational attachment than by formal innovation processes, particularly within bureaucratic academic systems. The implication is clear: university leaders must prioritize strengthening knowledge systems and organizational commitment as primary drivers of sustainable performance.